The New Guinness Book of Records 1995 - Matthews, Peter, editor 243683; McWhirter, Norris, 1925-2004 editor 386864 (Enfield, England : Guinness Publishing Ltd, 1994)
Every day new records are set all around the world. Some occur through natural growth, some where existing records need updating, some from exciting new discoveries in science and technology. Most, however, come from the striving by men and women to set new standards. Such achievements may come in areas of widespread interest, while others can only be fully appreciated by those with similar specialist skills. Our collection of extremes, in, on and beyond the Earth has, we know, considerable appeal to peoples of all nations, and, of course, our book appears in many languages. Records in all categories can be fascinating, inspiring a variety of emotions, including incredulity, wonder and sorrow, but our aim is to inform and educate and to settle arguments which develop when people discuss facts.